Identification of Novel Genes Regulated by Chorionic Gonadotropin in Baboon Endometrium during the Window of Implantation - Sherwin, J. R. A. (2007)
Chorionic Gonadotrophin is an early embryo derived signal that is known to support the Corpus Luteum. An in-vivo baboon model was used to study the direct actions of hCG on the endometrium, during the peri-implantation period. Endometrial gene expression was analyzed using microarrays. The endometrial biopsies were taken from hCG treated (n=5) and control (n=6) animals on day 10 after ovulation. Class comparison identified genes whose transcript levels differed between control and hCG treated samples (48 increased, 13 decreased in mean expression level more than 2.5 fold, p<0.01). Real time PCR of transcript abundance confirmed up regulation of several of these, including SerpinA3, Matrix Metalloproteinase 7 (MMP-7), Leukemia Inhibitory Factor (LIF), Interleukin-6 and Complement 3 (p¡Ü0.05). Analysis of protein abundance in endometrial flushings showed increased LIF and IL-6 protein in uterine flushings from hCG treated animals compared to controls. Complement C3 and Superoxide dismutase 2 (SOD) that were also upregulated, were further evaluated by immunocytochemistry. C3 showed a marked increase in stromal staining in response to hCG, whilst SOD localization was most markedly increased in the glandular epithelial cells. Expression of Soluble Frizzled Related Protein 4, the most highly down regulated gene, was also validated by PCR. Our experiments have shown that hCG induces alterations in the endometrial expression of genes that regulate embryo attachment, extracellular matrix remodeling and the modulation of the immune response around the implanting blastocyst. Several of these genes, including LIF and gp130 have been shown to be essential for implantation in other species. This study provides strong evidence that the pre-implantation embryo itself influences the development of the receptive endometrium via secreted paracrine signals.